Traumatic brain injury and intimate partner violence: Addressing knowledge and service gaps among indigenous populations in Canada. Issue 2 (12th July 2019) - Haag, Halina (Lin); Biscardi, Melissa; ,; Smith, Noel (Natalia); MacGregor, Nneka; Colantonio, Angela
Abstract: Background: Traumatic brain injury (TBI) is a serious consequence of intimate partner violence (IPV) that is often overlooked. In the case of Indigenous women in Canada the challenges are broad, multidimensional, and left almost entirely unexplored. Given the elevated rates of violence and injury experienced by women exposed to IPV and the increased levels of physical assault among Indigenous women in Canada, it is important to understand the unique experiences and service needs of these women. This study sought to identify barriers and facilitating factors for TBI-sensitive service provision for Indigenous women experiencing IPV. Method: As part of a larger national stakeholder consultation process to develop a TBI educational toolkit for IPV service providers, input from Indigenous stakeholders was specifically sought to allow for insights into unique challenges and strengths related to this population. Interviews and focus groups were conducted with IPV direct-service providers, support professionals, and advocates working with Canadian First Nations and Inuit women. Findings: Findings suggest that multiple intersections of marginalization, shame and stigma, and colonization, coupled with significant barriers to service provision in remote communities are such that solutions generated for urban-based settler populations are ineffective. Conclusions: Recommendations include a widespread educational campaign to raise awareness of the seriousness of TBI among Indigenous women exposed to IPV. Education is particularly important among healthcare and direct service providers, survivors and their families and communities, legal professionals and child protection agencies, and Indigenous and settler government bodies. Future research should focus on expanding our understanding of this complex issue and developing culturally sensitive, community-based supports.